A Study of Early post-operative wound complications of spina bifida aperta repair “Incidence and Risk Factors” - Ali K. AL-Shalchy; Wameedh Q. Abdul-hussein (مجلة كلية الطب, 2018)
Background: Myelomeningocele is the single most common congenital anomaly that affects the CNS and vertebral column. The third world countries having a higher incidence. The management is usually surgical with relative high incidence of complications. Objectives: to evaluate the possible risk factors that may predispose to early wound complications of myelomeningocele. Methods: This prospective study was carried out in the Surgical Specialization Hospital in Medical City Complex - Baghdad from 2009-2012. 147 cases were included in the study. Requested data were gestational age, type of delivery, gender, age at operation, type of suturing of the wound, tension of suturing, duration of operation, site of the lesion, ruptured vs non ruptured myelomeningocele, associated shunting, peri-operative stay in hospital and associated jaundice. Result: Forty four (44 %) of the total developed complications. All premature infants developed complications. Hydrocephalic cases was associated with higher rate of complication (86%). Type of delivery, age at operation, duration of operation, ruptured cases and site of the lesion were not associated with complications. Conclusion: Myelomeningocele was predominantly affecting female. Most of the complications were wound infection with or without dehiscence, CSF leakage or seroma.